2018
DOI: 10.1002/cjce.23084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ni modification on NO‐CO reaction with MnOx‐CuO/TiO2 catalysts

Abstract: Ni modified MnOx‐CuO/TiO2 catalysts were synthesized by the sol‐gel method and investigated for NO‐CO reaction. The results showed that 0.05Ni‐Mn‐Cu/TiO2 (the Ni/Ti molar ratio was 0.05) had the highest NO conversion efficiency with a maximum value of 85.4 % at 350 °C, which was 10 % higher than that of Mn‐Cu/TiO2. XPS analysis showed that more chemisorbed oxygen formed on the Ni‐modified catalyst surface, which could act as active sites for CO adsorption and oxidation. CO‐TPD results confirmed that the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Oxygen in the gas phase is transferred inside the catalyst to renew the surface oxygen, thus completing the catalytic cycle. [26][27][28] The kinetics of SCR denitrification can be divided into three processes: the adsorption process, the catalytic reduction process, and the desorption process. According to the gas-solid surface catalytic reaction mechanism, the reaction kinetics equations are as follows:…”
Section: Mechanism Model Of Scrmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen in the gas phase is transferred inside the catalyst to renew the surface oxygen, thus completing the catalytic cycle. [26][27][28] The kinetics of SCR denitrification can be divided into three processes: the adsorption process, the catalytic reduction process, and the desorption process. According to the gas-solid surface catalytic reaction mechanism, the reaction kinetics equations are as follows:…”
Section: Mechanism Model Of Scrmentioning
confidence: 99%
“…Oxygen in the gas phase is transferred inside the catalyst to renew the surface oxygen, thus completing the catalytic cycle. [ 26–28 ] The kinetics of SCR denitrification can be divided into three processes: the adsorption process, the catalytic reduction process, and the desorption process. According to the gas–solid surface catalytic reaction mechanism, the reaction kinetics equations are as follows: dθNH3italicdt=rnormalarnormaldrNOrox dCNH3italicdt=ΩNH3rnormaldrnormala dCNOitalicdt=ΩNH3rNO dCnormalN2italicdt=ΩNH3rNO+0.5rox where θNH3 is the coverage of adsorbed NH 3 on the catalyst, r a is the adsorption rate, r d is the desorption rate, r NO is the denitration reaction rate, r ox is the oxidation rate of adsorbed NH 3 , ΩNH3 is the adsorption capacity of the catalyst for NH 3 , and C is the concentration of each gas in the gas phase.…”
Section: Scr System Modellingmentioning
confidence: 99%
“…Zhang et al . synthesized a MnO x ‐CuO/TiO 2 catalyst modified with Ni and found that the highest NO conversion reached 85.4% at 350 °C . However, most studies were carried out under a simple reaction atmosphere, which contained only NO and CO. Few reports have examined reaction atmospheres approaching typical automobile exhaust .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Liu et al investigated NO removal with CO over CuO-CoO x supported on Ce 0.67 Zr 0.33 O 2 , and showed that when the reaction temperature was >350 ∘ C, conversions of NO and CO both achieved 90% under the gas hourly space velocity (GHSV) of 24 000 h −1 . 25 Zhang et al synthesized a MnO x -CuO/TiO 2 catalyst modified with Ni and found that the highest NO conversion reached 85.4% at 350 ∘ C. 26 However, most studies were carried out under a simple reaction atmosphere, which contained only NO and CO. Few reports have examined reaction atmospheres approaching typical automobile exhaust. 27 Satsuma et al evaluated the activity of a Fe-Ni/CeO 2 catalyst and reported that simultaneous removal of NO, CO and C 3 H 6 was attained above 300 ∘ C. 28 Kang et al loaded Ni-Cu alloy onto Mg-Al mixed oxides and synthesized a Ni 0.3 Cu 0.2 /2MgO·1/2MgAl(2)O(4) catalyst, which showed a high catalytic activity for a simulated automotive exhaust, especially for the oxidation of HCs in a reducing atmosphere.…”
Section: Introductionmentioning
confidence: 99%